Elucidation and active ingredient identification of aqueous extract of Ficus exasperata Vahl leaf against bisphenol A-induced toxicity through in vivo and in silico assessments. - Adeyemi, O.E.; Jaryum, K.H.; Johnson, T.O. (In silico pharmacology, 2024)
Bisphenol A (BPA), an endocrine-disrupting chemical, poses significant health problems due to its induction of oxidative stress, inflammation, etc. Whereas Ficus exasperata Vahl leaf (FEVL) was reported for its ethnopharmacological properties against several ailments owing to its antioxidant, anti-inflammatory properties, etc. Here, we aim to elucidate and identify the bioactive compounds of aqueous extract of FEVL (AEFEVL) against BPA-induced toxicity using in vivo and in silico assessments. To determine the BPA toxicity mechanism and safe doses of AEFEVL, graded doses of BPA (0-400 ?M) and AEFEVL (0-2.0 mg/10 g diets) were separately fed to flies to evaluate survival rates and specific biochemical markers. The mitigating effect of AEFEVL (0.5 and 1.0 mg/10 g diet) against BPA (100 and 200 ?M)-induced toxicity in the flies after 7-day exposure was also carried out. Additionally, molecular docking analysis of BPA and BPA-o-quinone (BPAQ) against selected antioxidant targets, and HPLC-MS-revealed AEFEVL compounds against Keap-1 and IKK? targets, followed by ADMET analysis, was conducted. Emergence rate, climbing ability, acetylcholinesterase, monoamine oxidase-B, and glutathione-S-transferase activities, and levels of total thiols, non-protein thiols, nitric oxide, protein carbonyl, malondialdehyde, and cell viability were evaluated. BPA-induced altered biochemical and behavioral parameters were significantly mitigated by AEFEVL in the flies (p < 0.05). BPAQ followed by BPA exhibited higher inhibitory activity, and epigallocatechin (EGC) showed the highest inhibitory activity among the AEFEVL compounds with desirable ADMET properties. Conclusively, our findings revealed that EGC might be responsible for the mitigative effect displayed by AEFEVL in BPA-induced toxicity in D. melanogaster.